Performance of early literacy students in cognitivelinguistic skills during the pandemic - Stolf, Mariana Taborda [UNESP]; Santos, Natália Lemes dos [UNESP]; D’Angelo, Ilaria; Bianco, Noemi Del; Giaconi, Catia; Capellini, Simone Aparecida [UNESP] (Faculdade de Filosofia e Ciências, 2021)
Introduction: the Covid-19 pandemic made discrepancies between the different educational realities more evident for schoolchildren in the beginning of literacy. Objective: to characterize the performance of cognitivelinguistic skills of students in early literacy phases during the pandemic. Methods: twenty-two elementary school students participated in this study, distributed in GI 1st year students and 2nd year GII students, submitted to the application of the Cognitive-Linguistic Skills Assessment Protocol for students in the initial stage of literacy. Results: students from GI and GII showed average performance for writing the name and writing the alphabet in sequence. The GI presented a refusal response for the subtests of word dictation, pseudoword dictation and picture dictation, word repetition and visual sequential memory of shapes and poor performance for alphabet recognition in random order and average performance for alphabet recognition in sequence. GII showed lower performance for the subtests of word dictation, pseudoword dictation, picture dictation and superior performance for alphabet recognition in random order, alphabet in sequence and visual sequential memory of shapes. Discussion: the appropriation of the letter-sound relationship mechanism raises questions, since it evidenced the difficulty of all students in cognitive-linguistic skills necessary for the full development of reading and writing in an alphabetic writing system such as Brazilian Portuguese. Conclusion: students in the 1st and 2nd years showed lower performance in cognitive-linguistic skills important for learning reading and writing.
Keywords: Child development; Education; Learning; Literacy; Pandemic